Pasantía en la empresa Ivory Construcciones SAS que permita el desarrollo de la metodología adecuada para la planificación de costos del proyecto - Arcila Sánchez, Mateo (Ingeniería Civil, 2024)
Abstract: This work is focused on proposing cost planning different from the traditional one, proposed in virtual environments that adjusts to the requirements of the company Ivory Construcciones SAS, for its development, the current needs of the company are identified and different backgrounds are investigated and theoretical frameworks for implementing methodologies in cost planning. Taking into account the considerable improvements that can be achieved with the use of virtual technologies such as Construction Information Modeling (BIM), the aim is to demonstrate how this methodology is the best option for the company Ivory Construcciones SAS. For this reason, modeling of the specific structure of the tower is carried out, with the aim of comparing the results between the initial budget, what was actually executed and the calculations obtained by the BIM software, and to demonstrate how this methodology is much more precise. . to the traditional one.